MODEL OF INTERACTIONS AND PHASE STATES IN THE DISTRIBUTION OF THE FREQUENCY RESOURCE IN THE GROUPING OF RADIO ELECTRONIC MEANS OF A 5G MOBILE COMMUNICATION NETWORK - Sielivanov, Konstantyn; Muliar, Bohdan; Kolyadenko, Yulia; Moskalets, Mykola (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2021)
Subject: interaction models and phase states in the distribution of the frequency resource in the grouping of radio electronic means of the 5G mobile communication network. Purpose: development of a dynamic model of multiple interactions of n-elements of a complex 5G mobile communication system, which takes into account the nature of inter-element connections and phase states in the group use of the frequency resource. Tasks: on the basis of a complex model of an n-element system with multiple interactions, to develop a mathematical model for describing the electromagnetic environment of a grouping of radio electronic means in a state space with a group use of a frequency resource; to analyze the phase states of interaction of the elements of the grouping system of radio-electronic means of the mobile communication system in which they can function without deteriorating the quality indicators, which reflect the total level of the group influence of the emitting elements on the receiving devices, under conditions of optimal distribution of the frequency resource. Methods: mathematical method of the state space of the system, which describes the nonlinear nature and phase states of the system, taking into account the intensity of the interaction of its elements. Results: A mathematical model of the electromagnetic environment of a grouping of radio-electronic devices based on the Volterra model has been developed, which characterizes their nonlinear nature of interactions in the group use of the frequency resource. A recurrent expression is obtained for modeling the assessment of the aggregate nature of electromagnetic interactions in a group of radio-electronic means. Modeling of the dynamics of interaction and phase states of the grouping of radioelectronic devices in the group use of the frequency resource has been carried out. Conclusions: It is shown that using a model that simulates the dynamics of interactions of a group of radioelectronic, it is possible to analyze its state in the future. This model makes it possible to analyze the grouping of radio-electronic means with different, specific parameters of individual types of radio electronic devices, the nature and intensity of their interaction in the grouping with the current distribution of resources.